REPRESENTASI KRITIK SOSIAL DALAM TAYANGAN STAND UP COMEDY INDONESIA (ANALISIS SEMIOTIKA DEKONSTRUKSI) - Burhanuddin, Burhanuddin (Komodifikasi, 2018)
This study entitled "Representation of Social Criticism in Display of Stand Up Comedy Indonesia (The Analysis Semiotics Deconstruction)". This study addresses two main issues, namely: (1) Representation of social criticism in stand-up comedy shows Indonesia. (2) The meaning of the representation of social criticism contained in stand-up comedy shows Indonesia. The purpose of this study was to determine how the representation of the social criticism in stand-up comedy, delivered and to know the meaning of the representation of social criticism in the stand-up comedy shows Indonesia. This study is an analysis of media texts by using a model of semiotic deconstruction of Jacques Derrida. Data collection techniques in this study is documentation techniques. Data analysis techniques in this study, carried out in three stages: description, analysis, and interpretation. The results showed that the material from Abdur within a few appearances in the competition stand up comedy Indonesia, the first preshow edition, Abdur - "Di-'Folbek 'Raditya Dika", show 4th "Handphone Sumber Kecelakaan", show 6th "Orasi dari Timur", and show 9th "Pe Es Ka Kupang". Born by the socio-cultural context behind it, namely: 1). The first preshow edition (Di-Folbek Raditya Dika) is motivated by the phenomenon of educational inequality that occurred in Indonesia, especially in the eastern part which gives the impression that the government "discriminates" and do not give good attention to education for children in eastern Indonesia; 2). 4th edition of the show (Handphone Sumber Kecelakaan) is motivated by the phenomenon than government services for people in underdeveloped areas that led to the development of the area is also slow. 3). 6th edition of the show (Orasi dari Timur) against the backdrop of the observation of Abdur against his apathetic society in electoral participation by large numbers vote. This issue made the government increasingly difficult to get connected with the people they lead. 4). Show 9th edition (Pe eS Ka Kupang) is based upon the phenomenon of inequality of development that occurred in Indonesia. Western Indonesia who continue to receive development funds large intake is inversely proportional to the effort to develop eastern Indonesia which is still very far from prosperous.